Aspects regarding human capital and its influence on the competitiveness of firms in the European Union - Larisa Pantea (CES Working Papers, 2019)
Human capital represents the source of competitive advantage of a firm. The importance of human capital is acknowledged by firms. However, in an increasingly complex and turbulent environment many organizations face a lot of issues regarding the attraction, retaining and development of their most valuable asset. The approach chosen to solve above mentioned issues influences the competitiveness of the firm. The goal of the paper is to analyse the level and extent of theoretical research regarding the influence of human capital on the competitiveness of the firms, as well as issues related to firms' human capital development. Moreover, the paper presents the results of studies conducted in different European countries (comprising United Kingdom, Ireland, Netherlands and Sweden) regarding the relationship between investment in employee training and the effects on company performance. It elucidates that training generates positive effects on sales, value added, productivity, net profitability etc. Although the link between investment in human capital and company's performances is evident, the reciprocal connection - between companies' investment activities and skills of employees was pointed out.
Keywords: 330; human capital; general training; specific training; firm's knowledge; company performance